Variable to variable crossover in GA to solve PAPR reduction in OFDM systems - U-Thong, Sutud; Pradabpet, Chusit; La-Inchua, Jaraspat; Chivapreecha, Sorawat; Soontornwong, Parinya (My University, 2014)
The hybrid of partial transmit sequences (PTS) and cascade adaptive peak power reduction (CAPPR) methods have been used to reduce peak to average power ratio (PAPR) of orthogonal frequency division multiplexing (OFDM) system. When number of sub-block increases, PAPR is getting small. However, the calculation cost of its selection must be considerably large. We introduce variable to variable crossover in GA, the total calculation cost becomes drastically reduced. The parameter for simulation used standard WLAN in IEEE 802.11a system. In simulation results, the proposed method shows the improvement performance PAPR and bit error rate (BER) of an OFDM system.